The Effect of Intra-articular Injection of Betamethasone Acetate/Betamethasone Sodium Phosphate at the Knee Joint on the Hypothalamic-Pituitary-Adrenal Axis: A Case-Controlled Study. (October 2013) - Habib, George; Artul, Suheil; Chernin, Mark; Hakim, Geries; Jabbour, Adel
Background: Intra-articular corticosteroid injection (IACI) of betamethasone depot preparation is a popular procedure at the knee joint. Intra-articular corticosteroid injection in general could be associated with systemic effects including suppression of the hypothalamic-pituitary-adrenal axis. There are nearly no reports on the effect of IACI of betamethasone at the knee joint on the hypothalamic-pituitary-adrenal axis. Method: Consecutive patients attending the rheumatology or orthopedic clinic with osteoarthritic knee pain who were not responding satisfactorily to medical and physical therapy were allocated to group 1 after consent and given IACI of 6 mg of betamethasone acetate/betamethasone sodium phosphate. After completion of this part, consecutive age- and sex-matched patients were allocated to group 2 and given intra-articular injection of 60 mg of sodium hyaluronate. Demographic, clinical, laboratory, and radiographic variables were documented. Just before the knee injection and 1, 2, 3, 4, and 8 weeks later, patients had 1-μg adrenocorticotropin hormone (ACTH) stimulation test. Secondary adrenal insufficiency (SAI) was defined as levels of less than 18 µg/dL and lack of a rise of more than 6 µg/dL in serum cortisol level, 30 minutes after the ACTH stimulation test. Patients were blinded to the injected material, and all injections were ultrasound guided. Results: Twenty patients were enrolled in each group and equally divided between the 2 sexes. The mean age of the patients was approximately 54 years in both groups. No significant difference in any variable was seen between the 2 groups. One patient only from group 1 (the betamethasone group) had SAI 3 weeks after the IACI compared to none in the control group ( P > 0.9999). His serum cortisol level 30 minutes after the ACTH stimulation was 17 µg/dL, with a rise of 3 µg/dL from baseline. Conclusion: Intra-articular corticosteroid injection of 6 mg of betamethasone acetate/betamethasone sodium phosphate at the knee joint was not significantly associated with SAI at the time points tested.